Effect of concussions on National Football League quarterback performance - Heintz, E. C.; Foret, E. F.; Foreman, J. J. (International Journal of Kinesiology & Sports Science, 2020)
Background: Sports-related concussion (SRC) rates are higher in American football than any other sport; therefore, the effects of SRCs on professional football players is a prevalent topic. Previous research has shown that sustaining an SRC has negative financial and overall career outcomes for athletes and may cause performance decrements after an athlete returns to play, however, the results of previous research regarding athlete performance after returning from an SRC are mixed. While some studies found that player performance in the National Football League (NFL) was unaffected upon returning from an SRC, evidence also suggests significant scoring reductions in offensive players. Although previous research has found that NFL running backs and wide receivers perform at levels similar to their performance before sustaining an SRC, little is known about quarterback performance after an SRC. There is also evidence that SRCs decrease neurocognitive performance, a quality that is crucial, especially for quarterbacks. Objective: The purpose of this study is to examine changes in NFL quarterback performances upon return to play from an SRC. Method: Quarterback ratings (QBRs) and concussion data from 2012-2015 were used to determine if changes occurred in NFL quarterback performance following an SRC. Results: QBRs decreased by 13.3 points (p = 0.014) after quarterbacks return from an SRC. Conclusions: Changes in on-field performance for NFL quarterbacks after sustaining an SRC could be the result of neurocognitive decrements that impact quick reaction and decision-making skills, which may have greater impacts on quarterbacks than other positions.